Pengembangan Sistem Transformasi dan Konversi Data Berbasis Web Menggunakan Arsitektur RESTful API - Deborah Kurniawati; Adi Kusjani; Robby Cokro Buwono; Muhammad Aldo Ridhoni (Bulletin of Computer Science Research, 2025)
Heterogeneous data management often faces challenges such as format inconsistency, high latency, and lack of automation, leading to inefficiencies and errors in data transformation. This research aims to develop a web-based system to automate data transformation and conversion across formats using a Representational State Transfer (RESTful) Application Programming Interface (API) architecture, with a Mithril.js frontend and Go backend. An experimental and system development approach was employed, comprising three stages: client-server architecture design, implementation, and testing. The system provides 11 primary API endpoints, such as /api/tasks and /api/transformations, to manage tasks and data transformations. The Single Page Application frontend offers intuitive navigation with menus for task management, data sources, and activity logs. Functional testing on Comma-Separated Values, JavaScript Object Notation, and SQLite formats yielded accurate transformations, including text prepending, data type conversion, and lowercase normalization. Performance evaluation using Google Lighthouse recorded a median score of 85, indicating high performance. The system enhances efficiency and accuracy compared to manual methods, supporting cross-platform interoperability. However, limitations include support for only simple tabular formats and lack of security features. This research offers a lightweight solution for data transformation, with potential applications in organizational data integration and business analytics.